Water-resistant paper mulberry leaf protein wood adhesive and preparation method thereof
By adopting alkaline heat activation, lignin epoxy polymer cross-linking and urea composite modification technology, water-resistant mahogany protein wood adhesives are prepared, which solves the problem of insufficient wet bonding strength of existing adhesives and achieves efficient Improved gluing performance and is suitable for industrial applications.
Patent Information
- Application Number
- CN202411840869.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-14
AI Technical Summary
The existing mahogany protein wood adhesives have insufficient wet bonding strength, which is difficult to meet the needs of industrial applications. The existing adhesive production process technology is not suitable for the preparation of high-quality mahogany protein wood adhesives.
A water-resistant mulberry protein wood adhesive is prepared by alkaline heat activation, lignin epoxy polymer cross-linking and urea composite modification technology. The method includes mixing the mahogany protein extract with a protein denaturant, a dispersion medium and a crosslinker, and reacting at a constant temperature to improve the bonding strength.
The wet glue strength of mahogany protein wood adhesive has been significantly improved to reach 1.48 MPa, far exceeding the highest value reported in the existing literature. The product has excellent water resistance and mechanical strength, which is suitable for application in the plywood industry.
Smart Images

Figure CN119432319A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a protein adhesive, in particular to a water-resistant paper mulberry leaf protein wood adhesive and a preparation method thereof. Background Art
[0002] my country is the largest producer, consumer and trader of wood-based panels, and adhesives are the most important chemical raw materials in the wood-based panel industry. In recent years, the consumer demand for green and environmentally friendly biomass adhesives to replace mainstream petroleum-based adhesives has been growing. A wide variety of biomass adhesives have been successfully prepared based on biomass resources such as protein, lignin, and starch, but there are still problems such as high development costs and insufficient bonding performance, which restrict their large-scale application.
[0003] Protein adhesive is one of the most widely used biomass adhesives. At present, the raw materials used for protein adhesives at home and abroad are mainly soybean protein. Soybean is one of the main food resources. The large-scale application of soybean protein in the field of wood-based panel adhesives will face the problem of limited raw material supply. Therefore, it is necessary to develop other sources of protein raw materials with good promotion and application prospects. Broussonetia papyrifera ) leaf protein content is as high as 18~26%, far exceeding the average protein content of other types of leaves, and can be used as an ideal substitute for soybean protein in the preparation of adhesives. Paper mulberry is widely distributed in my country and has abundant resources. A large hybrid paper mulberry planting base has been built. It has the advantages of strong adaptability, fast growth, strong germination and tillering ability, and tolerance to pruning. Therefore, its leaves have become the most important part to be utilized, which can meet the demand for a continuous and stable supply of protein raw materials for adhesives.
[0004] However, as a new source of protein raw materials for adhesives, paper mulberry leaf protein has the characteristics of a high proportion of hydrophobic amino acids and poor water solubility compared with soybean protein. Therefore, the existing adhesive production process technology developed around soybean protein raw materials is not suitable for the preparation of high-quality paper mulberry leaf protein wood adhesives. Wu et al. (Wu, Z., Xi, X., Pizzi, A.et al. Effects of Broussonetia papyrifera leaf cutting modes on bondingperformance of its protein-based adhesives. European Journal of Wood and WoodProducts. 2020, 78: 461-470.) used urea and cross-linking agent to modify paper mulberry leaf protein to prepare wood adhesives, focusing on the effects of leaf cutting height and leaf cutting frequency on adhesive performance. However, the above literature did not conduct in-depth research on key factors such as paper mulberry protein extraction process and composite modification technology that determine the quality of adhesives. The wet bonding strength of the prepared adhesive was only 0.28~0.75MPa, which was difficult to meet the needs of industrial applications, and the comprehensive performance needed to be further improved. In order to realize the large-scale application of paper mulberry leaf protein in the field of wood adhesives, it is urgently necessary to build a new adhesive production technology system based on the characteristics of paper mulberry leaf protein. Summary of the invention
[0005] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a water-resistant paper mulberry leaf protein wood adhesive with excellent comprehensive performance and a preparation method thereof.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows: A water-resistant paper mulberry leaf protein wood adhesive, comprising the following components in parts by weight: Protein denaturant I 2.4 parts; Protein denaturant II 0.3 parts; 120 parts of dispersion medium; 30 parts of Broussonetia papyrifera leaf protein extract; 30 parts of crosslinking agent.
[0007] Preferably, the protein denaturant I mentioned above is sodium hydroxide; the protein denaturant II is urea; the dispersion medium is water; and the cross-linking agent is lignin epoxy polymer.
[0008] Preferably, the preparation method of the paper mulberry leaf protein extract described above mainly comprises the following steps: S1.1 Wash fresh paper mulberry leaves, mix with water, add sodium chloride, crush and pulp, filter and collect the filtrate; S1.2 Adjust the pH value of the filtrate and heat the reaction at a constant temperature of 75°C; S1.3 After the reaction is completed, the leaf protein extract of the paper mulberry tree is obtained by precipitation, centrifugation, drying, grinding and sieving, wherein the sieving is performed through a sieve of 200 mesh or above.
[0009] Preferably, in the above step S1.1, the mass ratio of the paper mulberry leaves to water is 1:2, and the amount of sodium chloride used is 0.17% of the mass of the paper mulberry leaves; The pH value of step S1.2 is 6, and the heating time is 25 minutes.
[0010] Preferably, the preparation method of the above-mentioned lignin epoxy polymer mainly comprises the following steps: S2.1 The enzymatically hydrolyzed lignin (EHL) was mixed with a sodium hydroxide solution, and reacted at 50 °C for 1 h. After filtering, the pH of the filtrate was adjusted to 2-3, and the precipitate was allowed to stand for 24 h. The precipitate was separated, washed with hot acid water at pH 2, and freeze-dried to obtain purified enzymatically hydrolyzed lignin (EHL). S2.2 The purified enzymatically hydrolyzed lignin (EHL) obtained in step S2.1 was mixed with sodium hydroxide solution and ethylene glycol diglycidyl ether (EGDE), and the mixture was heated at 30°C and stirred for 4 h to obtain lignin epoxy polymer (EPL).
[0011] Preferably, the mass fraction of the sodium hydroxide solution in steps S2.1 and S2.2 above is 1%; In the step S2.1, the mass ratio of enzymatically hydrolyzed lignin (EHL) to sodium hydroxide solution is 1:25; In the step S2.2, the mass ratio of purified enzymatically hydrolyzed lignin (EHL), sodium hydroxide solution, and ethylene glycol diglycidyl ether (EGDE) is 1:10:5.
[0012] Preferably, the above-mentioned dispersion medium is deionized water.
[0013] The preparation method of the water-resistant paper mulberry leaf protein wood adhesive described above mainly comprises the following steps: (1) Mix protein denaturant I, protein denaturant II and dispersion medium, add paper mulberry leaf protein extract after fully dissolving, and heat at constant temperature for 1.5 h; (2) Add a cross-linking agent to the mixture obtained in step (1), and continue to heat the mixture at a constant temperature for 0.5 h to obtain a water-resistant paper mulberry leaf protein wood adhesive.
[0014] Preferably, the temperature of the heating reaction in the above steps (1) and (2) is 60°C.
[0015] Technical principle of the present invention: Alkali-thermal activation successfully opened the secondary, tertiary and quaternary structures of the paper mulberry leaf protein, broke the macromolecular chains and released active groups such as hydroxyl, amino and carbonyl groups, and destroyed the hydrophobic amino acids to form a protein solution. It opened the spherical structure of the paper mulberry leaf protein at the microscopic level, increased the degree of disorder, and made the protein structure looser, providing reaction sites for the subsequent addition of cross-linking agents. At this time, the system contains a large number of active groups.
[0016] The addition of lignin epoxy polymer crosslinker provides epoxy groups, which react with active groups on protein molecules such as hydroxyl, amino, carbonyl, and carboxyl to form a stable crosslinking structure, increasing the crosslinking density and reaction degree. This is also the main source of bonding strength of protein adhesives.
[0017] Urea composite modification increases the number of active groups in the system through its unique dissociation properties, thereby affecting the degree of reaction between the crosslinker and the amino acid residues. At the same time, due to the secondary destruction of protein molecules by composite modification, the viscosity of the system can be reduced to a certain extent. The high viscosity of protein adhesives often hinders their penetration into wood, which is not conducive to improving the bonding strength. In short, composite modification has the effect of enhancing viscosity reduction. Physically, it improves the penetration effect of protein adhesives by reducing viscosity. In the chemical structure, it strengthens the dissociation of protein residues to provide more reaction sites, thereby improving the bonding strength by increasing the degree of crosslinking reaction.
[0018] In summary, the present invention comprehensively utilizes the technical principles of alkali thermal activation, lignin epoxy polymer cross-linking and enhanced composite modification to construct an efficient wood adhesive synthesis technology system for paper mulberry leaf protein.
[0019] The advantages and beneficial effects of the present invention are as follows: 1. The present invention uses paper mulberry leaf protein as the main raw material to prepare wood adhesive, develops a new source of raw materials for biomass-based wood adhesive, solves the problem of green raw materials and low-cost and sustainable supply, and also significantly improves the economic utilization value of paper mulberry resources.
[0020] 2. The present invention has developed a complete set of wood adhesive preparation technology system based on the characteristics of paper mulberry leaf protein, which has the advantages of simple synthesis process, environmentally friendly preparation process, strong product controllability, etc. The prepared environmentally friendly wood adhesive product has excellent water resistance and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 : Flow chart of the extraction process of paper mulberry leaf protein. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Example
[0023] A water-resistant paper mulberry leaf protein wood adhesive, comprising the following components in parts by weight: Protein denaturant I 2.4 parts; Protein denaturant II 0.3 parts; 120 parts of dispersion medium; 30 parts of Broussonetia papyrifera leaf protein extract; 30 parts of crosslinking agent.
[0024] Wherein, the protein denaturant I is 1% by mass sodium hydroxide; the protein denaturant II is urea; the dispersion medium is deionized water; and the cross-linking agent is lignin epoxy polymer.
[0025] The preparation method of the paper mulberry leaf protein extract mainly comprises the following steps: S1.1 Wash fresh paper mulberry leaves, mix them with water, add sodium chloride, crush and pulp them according to the conventional method, filter and collect the filtrate; the mass ratio of paper mulberry leaves to water is 1:2, and the amount of sodium chloride is 0.17% of the mass of paper mulberry leaves; Specifically, the crushing and beating is performed using a juicer for 10 minutes to fully destroy the cell walls of the leaves; when filtering, the leaves are filtered for more than 3 times using 100 mesh, 300 mesh, and 500 mesh gauze step by step until the filter residue is fully removed; S1.2 Adjust the pH value of the filtrate to 6 and heat the reaction at 75°C for 25 minutes; S1.3 After the reaction is completed, the paper mulberry leaf protein extract is obtained by conventional precipitation, centrifugation, drying, grinding and sieving. Specifically, during precipitation, it is placed in a 4°C refrigerator and allowed to stand for more than 24 hours; during centrifugation, the centrifugal speed is 8000 rpm and the centrifugal time is 10 minutes; during drying, the drying temperature is 50°C and the drying time is 48 hours; and the sieving is performed through a sieve of 200 mesh or above.
[0026] The preparation method of the lignin epoxy polymer mainly comprises the following steps: S2.1 The enzymatically hydrolyzed lignin (EHL) was mixed with a 1% sodium hydroxide solution at a mass ratio of 1:25, and the mixture was heated at 50°C for 1 h. After filtering, the pH of the filtrate was adjusted to 2-3, and the mixture was allowed to stand for 24 h. The precipitate was separated, washed with hot hydrochloric acid at pH 2, and freeze-dried to obtain purified enzymatically hydrolyzed lignin (EHL). S2.2 The purified enzymatically hydrolyzed lignin (EHL) obtained in step S2.1 was mixed with 1% by mass sodium hydroxide solution and ethylene glycol diglycidyl ether (EGDE) in a mass ratio of 1:10:5, and stirred at a constant temperature at 30°C for 4 h to obtain lignin epoxy polymer (EPL).
[0027] The preparation method of the water-resistant paper mulberry leaf protein wood adhesive mainly comprises the following steps: (1) Mix 2.4 parts of 1% sodium hydroxide, 0.3 parts of urea and 120 parts of deionized water, add 30 parts of the prepared paper mulberry leaf protein extract after fully dissolving, and heat at 60°C for 1.5 h; (2) Add 30 parts of the prepared lignin epoxy polymer to the mixture obtained in step (1), and continue to heat the mixture at 60° C. for 0.5 h to obtain a G-OH-U-EPL modified water-resistant paper mulberry leaf protein adhesive.
[0028] Comparative Example 1: Preparation of paper mulberry leaf protein adhesive without adding urea and lignin epoxy polymer.
[0029] 2.4 parts by mass of 1% sodium hydroxide and 120 parts of deionized water were mixed, and after fully dissolved, 30 parts of the paper mulberry leaf protein extract prepared in Example 1 were added, and the mixture was heated at a constant temperature of 60°C for 1.5 h to obtain a G-OH modified paper mulberry leaf protein adhesive.
[0030] Comparative Example 2: Preparation of paper mulberry leaf protein adhesive without added urea.
[0031] (1) Mix 2.4 parts by mass of 1% sodium hydroxide and 120 parts of deionized water, add 30 parts of paper mulberry leaf protein extract after fully dissolving, and heat at 60°C for 1.5 h; wherein the preparation method of paper mulberry leaf protein extract is the same as that in Example 1; (2) Add 30 parts of lignin epoxy polymer to the mixture obtained in step (1), and continue to heat the mixture at 60° C. for 0.5 h to obtain a G-OH-EPL modified paper mulberry leaf protein adhesive; wherein the preparation method of the lignin epoxy polymer is the same as that in Example 1.
[0032] Comparative Example 3: Preparation of paper mulberry leaf protein adhesive by replacing protein denaturant II with sodium sulfite.
[0033] (1) 2.4 parts by mass of 1% sodium hydroxide, 0.3 parts of sodium sulfite and 120 parts of deionized water were mixed, and after fully dissolved, 30 parts of paper mulberry leaf protein extract were added, and the mixture was heated at a constant temperature of 60° C. for 1.5 h. The preparation method of paper mulberry leaf protein extract was the same as that in Example 1. (2) Add 30 parts of lignin epoxy polymer (EPL) to the mixture obtained in step (1), and continue to heat the mixture at 60°C for 0.5 h to obtain a G-OH-SO3-EPL modified water-resistant paper mulberry leaf protein adhesive; wherein the preparation method of the lignin epoxy polymer is the same as that in Example 1.
[0034] Comparative Example 4: Preparation of paper mulberry leaf protein adhesive by replacing protein denaturant II with sodium dodecyl sulfate.
[0035] (1) 2.4 parts by mass of 1% sodium hydroxide, 0.3 parts of sodium dodecyl sulfate (SDS) and 120 parts of deionized water were mixed, and after fully dissolved, 30 parts of paper mulberry leaf protein extract were added, and the mixture was heated at a constant temperature of 60°C for 1.5 h; wherein the preparation method of paper mulberry leaf protein extract was the same as that in Example 1; (2) Add 30 parts of lignin epoxy polymer (EPL) to the mixture obtained in step (1), and continue to heat the mixture at 60°C for 0.5 h to obtain a G-OH-SDS-EPL modified water-resistant paper mulberry leaf protein adhesive; wherein the preparation method of the lignin epoxy polymer is the same as that in Example 1.
[0036] Comparative Example 5: The only difference from Example 1 is that the preparation method of the paper mulberry leaf protein extract is different. Specifically, the main operating steps of the preparation method of the paper mulberry leaf protein extract are as follows: S1.1 Wash fresh paper mulberry leaves, mix them with water, add sodium chloride, crush and pulp them in a conventional manner, filter and collect the filtrate; wherein the mass ratio of paper mulberry leaves to water is 1:5, and the amount of sodium chloride is 1.0% of the mass of the paper mulberry leaves; Specifically, the crushing and beating is performed using a juicer for 10 minutes to fully destroy the cell walls of the leaves; when filtering, the leaves are filtered for more than 3 times using 100 mesh, 300 mesh, and 500 mesh gauze step by step until the filter residue is fully removed; S1.2 Adjust the pH value of the filtrate to 5 and heat the reaction at 75°C for 30 min; S1.3 After the reaction is completed, the paper mulberry leaf protein extract is obtained by conventional precipitation, centrifugation, drying, grinding and screening. Specifically, during precipitation, it is placed in a 4°C refrigerator and allowed to stand for more than 24 hours; during centrifugation, the centrifugal speed is 8000 rpm and the centrifugal time is 10 minutes; during drying, the drying temperature is 50°C and the drying time is 48 hours; and screening is performed through a sieve of 200 mesh or above.
[0037] Comparative Example 6: The only difference from Example 1 is that the preparation method of the lignin epoxy polymer is different. Specifically, the main operating steps of the preparation method of the lignin epoxy polymer are as follows: S2.1 The enzymatically hydrolyzed lignin (EHL) was mixed with a 1% sodium hydroxide solution at a mass ratio of 1:25, and the mixture was heated at 50°C for 1 h. After filtering, the pH of the filtrate was adjusted to 2-3, and the mixture was allowed to stand for 24 h. The precipitate was separated, washed with hot hydrochloric acid at pH 2, and freeze-dried to obtain purified enzymatically hydrolyzed lignin (EHL). S2.2 The purified enzymatically hydrolyzed lignin (EHL) obtained in step S2.1 was mixed with 1% by mass sodium hydroxide solution and ethylene glycol diglycidyl ether (EGDE) in a mass ratio of 1:5:2, and stirred at a constant temperature at 30°C for 4 h to obtain lignin epoxy polymer (EPL).
[0038] Comparative Example 7: The only difference from Example 1 is that the preparation method of the paper mulberry leaf protein wood adhesive is different. Specifically, the main operating steps of the preparation method of the paper mulberry leaf protein wood adhesive are as follows: (1) 2.4 parts by mass of 1% sodium hydroxide, 0.3 parts of urea and 120 parts of deionized water were mixed, and after fully dissolved, 30 parts of paper mulberry leaf protein extract were added, and the mixture was heated at a constant temperature of 40°C for 1.5 h; wherein the preparation method of paper mulberry leaf protein extract was the same as that in Example 1; (2) Add 30 parts of lignin epoxy polymer to the mixture obtained in step (1), and continue to heat the mixture at 80°C for 0.5 h to obtain a paper mulberry leaf protein adhesive; wherein the preparation method of the lignin epoxy polymer is the same as that in Example 1.
[0039] Experimental example: The performance of the paper mulberry leaf protein adhesive prepared in Example 1 and Comparative Examples 1-7 was evaluated.
[0040] 1. Performance Testing Method 1) Viscosity: According to GB / T14074-2006 “Test methods for wood adhesives and resins”, the viscosity of the adhesive was measured using a digital viscometer; the measurement was performed three times in parallel (unit: mPa·s), and the average value was taken as the result.
[0041] 2) Solid content: Fold the tin foil into a round container according to the Petri dish, weigh the container and place it in a forced air drying oven to dry for 30 min, place it in a desiccator for 10 min and weigh it with an analytical balance, repeat this step until the difference between the two weights is less than 0.005 g, record it as m1; add 5 g of adhesive to the container, weigh the container again and record it as m2; dry the container in a forced air drying oven at 100 °C, then cool it to constant weight and record it as m3; repeat the test 3 times and take the average value, and calculate the solid content of the adhesive according to formula (1). (1) 3) pH value: According to the requirements of the national standard GB / T14074-2006 "Test methods for wood adhesives and resins", the pH value of the adhesive was measured using a digital pH meter, and the average value was taken after three repetitions.
[0042] 4) Gluing performance: Eucalyptus veneer (specification 200 mm×200 mm×1.7 mm) was selected, and after gluing and assembling, it was hot pressed into three-layer plywood. The process parameters were hot pressing temperature 140 ℃, glue coating amount 200 g / m 2 , hot pressing pressure 1.0-1.1 MPa, hot pressing time 10 min; according to the national standard GB / T 17657-2013, the bonding specimens were processed, one group of specimens were treated with equilibrium moisture content (called dry state), and the other group was immersed in 63°C water for 3h (called wet state); the treated bonding samples were subjected to tensile shear strength test using a universal mechanical testing machine to obtain the bonding strength and wood breakage rate of the specimens.
[0043] 5) Crystallinity: The cured adhesive powder sample was evenly spread in the mold and scanned using a Cu source in an X-ray diffractometer; the scanning wavelength of the instrument was set to 5-80°, the step length was 0.02°, the voltage was 40 kV, and the scanning rate was 5° / min to test the crystallinity of the sample.
[0044] 6) Surface hydrophobicity index: The paper mulberry leaf protein adhesive was diluted with PBS phosphate buffer (pH 7-7.4, 0.01 mol / L) to a gradient concentration of 0.20, 0.40, 0.60, 0.80, and 1.00 mg / mL; ANS fluorescent probe solution (8 mmol / L, prepared with the above PBS phosphate buffer) was prepared and ultrasonically shaken in the dark. Samples with different concentration gradients (4 mL) were mixed with 20 μL of ANS probe solution and reacted in the dark for 20 min; the samples were tested using a fluorescence spectrophotometer under the conditions of an excitation wavelength of 355 nm, an emission wavelength of 370 nm, an end wavelength of 650 nm, and a slit width of 5 nm. The protein mass concentration (mg / mL) gradient was selected as the index on the X-axis, and the fluorescence intensity was selected as the index on the Y-axis. The initial slope of the curve was the surface hydrophobicity index of the test sample.
[0045] 2. Results Analysis The test results of the embodiments and control examples are shown in Table 1. The unmodified paper mulberry protein adhesive (control example 1) has high viscosity, which makes it difficult to apply glue, and the wet bonding strength is only 0.28±0.13 MPa, with poor overall performance. After EPL cross-linking (control example 2), the performance is improved, but it still cannot meet the requirements of industrial application. Compared with the three composite modified adhesives (control examples 3, 4, and embodiment 1), the crystallinity and surface hydrophobicity index of the urea composite modified sample are significantly higher than those of the sodium sulfite and SDS modified samples, indicating that the number of stable network cross-linked structures formed inside is larger, the material system is more ordered, and the heat resistance and water resistance of the obtained adhesive product are better. Compared with control examples 5, 6, and 7, the process parameters of embodiment 1 (such as material-liquid ratio, pH, reactant mass ratio, reaction temperature, etc.) are better, and the bonding strength of the obtained adhesive product is better. Compared with Example 1, different extraction processes of paper mulberry leaf protein (Control Example 5) caused a decrease in the protein content in the extract, different reactant ratios in the preparation of the cross-linking agent lignin epoxy polymer (Control Example 6) caused a reduction in epoxy active groups, and different reaction temperatures in the preparation of the adhesive (Control Example 7) caused different degrees of protein denaturation, thereby affecting the cross-linking system of the adhesive product and resulting in a decrease in bonding strength.
[0046] Table 1 Comprehensive properties of paper mulberry protein adhesive Sample name Viscosity / mPa·s Solid content / % pH Dry bonding strength / MPa Wood breakage rate 1 / % Wet bonding strength / MPa Wood breakage rate 2 / % Crystallinity / % Surface hydrophobicity index Comparative Example 1 (G-OH) 29021 20.78 11.98 1.37±0.21 25±24 0.28±0.13 5±4 8.54 81.47 Comparative Example 2 (G-OH-EPL) 14393 23.41 12.12 1.33±0.22 46±22 0.68±0.08 11±9 16.28 575.40 <![CDATA[Comparative Example 3 (G-OH-SO3-EPL)]]> 2006 21.33 12.24 1.34±0.34 29±21 0.54±0.23 11±6 5.40 310.95 Comparative Example 4 (G-OH-SDS-EPL) 7545 22.63 11.81 1.42±0.26 27±23 1.04±0.22 23±20 9.42 262.75 Comparative Example 5 2044 24.58 11.98 1.15±0.20 35±20 0.74±0.18 20±12 7.08 389.38 Comparative Example 6 4953 23.84 11.94 1.17±0.17 28±19 0.68±0.12 13±8 8.93 395.34 Comparative Example 7 2784 25.49 11.86 1.30±0.20 42±18 0.89±0.16 22±18 7.18 458.93 Example 1 (G-OH-U-EPL) 6059 26.83 12.03 1.53±0.14 68±24 1.48±0.29 67±3 10.11 569.65 Compared with other control examples, the paper mulberry leaf protein adhesive prepared in Example 1 has the highest bonding strength, wood breakage rate and solid content, suitable viscosity and pH value, especially the wet bonding strength (1.48 MPa) is 97.3% higher than the highest value (0.75 MPa) reported in the existing literature. The product has excellent comprehensive performance and can be promoted and applied in the plywood industry.
[0047] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A water-resistant paper mulberry leaf protein wood adhesive, characterized in that: In parts by weight, it comprises the following components: Protein denaturant I 2.4 parts; Protein denaturant II 0.3 parts; 120 parts of dispersion medium; 30 parts of Broussonetia papyrifera leaf protein extract; 30 parts of crosslinking agent.
2. The water-resistant paper mulberry leaf protein wood adhesive according to claim 1, characterized in that: The protein denaturant I is sodium hydroxide; the protein denaturant II is urea; the dispersion medium is water; and the cross-linking agent is lignin epoxy polymer.
3. The water-resistant paper mulberry leaf protein wood adhesive according to claim 1, characterized in that: The preparation method of the paper mulberry leaf protein extract mainly comprises the following steps: S1.1 Wash fresh paper mulberry leaves, mix with water, add sodium chloride, crush and pulp, filter and collect the filtrate; S1.2 Adjust the pH value of the filtrate and heat the reaction at a constant temperature of 75°C; S1.3 After the reaction is completed, the leaf protein extract of the paper mulberry tree is obtained by precipitation, centrifugation, drying, grinding and sieving, wherein the sieving is performed through a sieve of 200 mesh or above.
4. The water-resistant paper mulberry leaf protein wood adhesive according to claim 3, characterized in that: In step S1.1, the mass ratio of the paper mulberry leaf to water is 1:2, and the amount of sodium chloride used is 0.17% of the mass of the paper mulberry leaf; The pH value of step S1.2 is 6, and the heating time is 25 minutes.
5. The water-resistant paper mulberry leaf protein wood adhesive according to claim 2, characterized in that: The preparation method of the lignin epoxy polymer mainly comprises the following steps: S2.1 The enzymatically hydrolyzed lignin was mixed with a sodium hydroxide solution, and the mixture was heated at 50 °C for 1 h. After filtering, the pH of the filtrate was adjusted to 2-3, and the mixture was allowed to stand for 24 h. The precipitate was separated, and the precipitate was washed with hot acid water at pH 2 and freeze-dried to obtain purified enzymatically hydrolyzed lignin. S2.2 The purified enzymatically hydrolyzed lignin obtained in step S2.1 is mixed with a sodium hydroxide solution and ethylene glycol diglycidyl ether, and the mixture is heated at 30° C. and stirred for 4 h to obtain a lignin epoxy polymer.
6. The water-resistant paper mulberry leaf protein wood adhesive according to claim 5, characterized in that: The mass fraction of the sodium hydroxide solution in steps S2.1 and S2.2 is 1%; In the step S2.1, the mass ratio of enzymatic lignin to sodium hydroxide solution is 1:25; In the step S2.2, the mass ratio of the purified enzymatically hydrolyzed lignin, the sodium hydroxide solution, and ethylene glycol diglycidyl ether is 1:10:
5.
7. The water-resistant paper mulberry leaf protein wood adhesive according to claim 2, characterized in that: The dispersion medium is deionized water.
8. A method for preparing a water-resistant paper mulberry leaf protein wood adhesive as claimed in any one of claims 1 to 7, characterized in that: The main steps are as follows: (1) Mix protein denaturant I, protein denaturant II and dispersion medium, add paper mulberry leaf protein extract after fully dissolving, and heat at constant temperature for 1.5 h; (2) Add a cross-linking agent to the mixture obtained in step (1), and continue to heat the mixture at a constant temperature for 0.5 h to obtain a water-resistant paper mulberry leaf protein wood adhesive.
9. The method for preparing a water-resistant paper mulberry leaf protein wood adhesive according to claim 8, characterized in that: The temperature of the heating reaction in steps (1) and (2) is 60°C.
Citation Information
Cited By
Hemp tree powder bio-based degradable material and preparation method thereof
CN120829627A
Ginseng composite freeze-dried powder and preparation method thereof
CN122557471A